PROFILING PRE-SERVICE TEACHERS’ PERCEPTION ON COURSEBOOK USED IN SENIOR HIGH SCHOOL - Selamat, Ely Heldydiana; Beda, Raimundus; Ekalia, Yulian Juita; Hame, Siprianus (Universitas PGRI Sumatera Barat, 2022)
This study focused on investigating six criteria of a coursebook, these are: content, vocabulary, methodology, visual aids, practice and testing, and objectives.This study employ mixed method research design in which quantitative and qualitative descriptive methods were mixed. The data were obtained through questionnaires and administered to 15 pre-service teachers of English Language Education Program of Unika Santu Paulus Ruteng as the participants of this study. The questionnaire were distributed to pre-service teachers through geogle form. Percentage and mean were calculated by using SPSS software program to describe the overall picture of how the pre-service seachers rated the textbook in terms of six criteria. The result of this study revealed that the pre-service teachers showed a positive response for each criteria that being analyzed in this study. They perceive that Buku Bahasa Inggris Kelas XI had been categorize as a good textbook in terms of content, vocabulary, methodology, visual aids, practice and testing, and objectives.The mean score of each item in this six criteria were over 3,00 which classified as good response. However, there were two items that showed a bad response from pre-service teachers such the presentation of new lexical item which covered only 2,87 and developmental of objectives should need more attention which covered only 2,93. Based on the result of this study, the writer concludedthat Buku Bahasa Inggris kelas xi is a good textbook for senior high school students especially for xi class because it categorize as a good textbook in terms of content, vocabulary, methodology, visual aids, practice and testing, and objectives.